The Abuja bombings: Boko Haram's reaction to President Buhari's actions. Issue 2 (2nd April 2016) - Onuoha, Freedom C.; George, Temilola A.
ABSTRACT: Since his inauguration on 29 May 2015, President Muhammadu Buhari has taken several practical, policy and diplomatic actions aimed at defeating the six-year long insurgency by Boko Haram terrorists in Nigeria. These actions have started to have a modest positive impact on reclaiming the territories previously held by the terrorists. Boko Haram has reacted by ramping up its attacks on soft targets and communities in the north-east. This article focuses on Boko Haram's bombing activities in Nigeria's capital city, Abuja. It shows that between 2011 and 2015, Boko Haram has staged nine bombings in Abuja, resulting in the deaths of at least 191 people, including suicide bombers. It argues that the October 2015 suicide bombings in Kuje and Nyanya, Abuja, represent Boko Haram's bold attempt to respond to President Buhari's counter-insurgency efforts. The article proposes the 'five Ds' approach as part of robust measures for combating the insurgency.